2017
DOI: 10.1175/jamc-d-16-0174.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Sources of Satellite Passive Microwave Rainfall Retrieval Systematic Errors Over Land

Abstract: Analyses of the Tropical Rainfall Measuring Mission (TRMM) satellite rainfall estimates reveal a substantial disagreement between its active [Precipitation Radar (PR)] and passive [TRMM Microwave Imager (TMI)] sensors over certain regions. This study focuses on understanding the role of the synoptic state of atmosphere in these discrepancies over land regions where passive microwave (PMW) retrievals are limited to scattering signals. As such the variability in the relationship between the ice-induced scatterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 85 publications
3
38
0
Order By: Relevance
“…For satellite-based precipitation estimation, passive microwave (PMW) and IR sensors are widely used. IR temperature is used to estimate rainfall based on the indirect relationship between cloud top temperature/height and surface precipitation (Joyce et al 2004) that is rather ambiguous (Petković and Kummerow 2017). PMW sensors at different wavelengths (e.g., 19 and 85 GHz) retrieve rainfall by employing both absorption and scattering properties of hydrometeors to the observed radiances at the top of the atmosphere (Cui et al 2016;Petković and Kummerow 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For satellite-based precipitation estimation, passive microwave (PMW) and IR sensors are widely used. IR temperature is used to estimate rainfall based on the indirect relationship between cloud top temperature/height and surface precipitation (Joyce et al 2004) that is rather ambiguous (Petković and Kummerow 2017). PMW sensors at different wavelengths (e.g., 19 and 85 GHz) retrieve rainfall by employing both absorption and scattering properties of hydrometeors to the observed radiances at the top of the atmosphere (Cui et al 2016;Petković and Kummerow 2017).…”
Section: Introductionmentioning
confidence: 99%
“…IR temperature is used to estimate rainfall based on the indirect relationship between cloud top temperature/height and surface precipitation (Joyce et al 2004) that is rather ambiguous (Petković and Kummerow 2017). PMW sensors at different wavelengths (e.g., 19 and 85 GHz) retrieve rainfall by employing both absorption and scattering properties of hydrometeors to the observed radiances at the top of the atmosphere (Cui et al 2016;Petković and Kummerow 2017). Nevertheless, precipitation studies related to mesoscale processes, particularly those associated with MCSs, have rarely been performed using the passive satellite-only precipitation products due to various issues including but not limited to coarse spatial and temporal resolutions, inconsistency in data availability, and errors in raw measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Over land, Zagrodnik and Jiang (2013) showed that TMI has an issue with higher rain-rate retrieval. Petković and Kummerow (2017) found that the frequency of occurrence for specific rainfall regimes containing different profiles of ice particles was essential for describing TMI-PR rainfall differences. The TMI estimation depends mostly on 85-GHz channels over land, which is more sensitive to ice particles (Gopalan et al 2010;Liu and Zipser 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, based on the WS algorithm, an algorithm for retrieving rain rates inside TCs by using MWRI 19 and 37 GHz Tbs is proposed. Since the upwelling radiation at higher frequencies is strongly affected by ice scattering, the retrieval uses lower frequencies where radiation is absorbed and re-emitted by liquid hydrometeors to obtain the information of the column-integrated liquid water [47]. High rain intensities not only change the atmospheric attenuation but also influence the sea surface dielectric properties in a complicated manner [48].…”
Section: Retrieval Algorithmmentioning
confidence: 99%